Chrysanthemum coronarium L.: A new pasture species for Mediterranean forage systems - Sulas L.; Re G.A.; Molle G.; Ligios S. (Dynamics and sustainability of Mediterranean pastoral systems, 1999)
Some spontaneous species growing as weeds in the cultivated area of Mediterranean basin countries can be considered a valuable source of feed with high palatability for dairy sheep. Chrysanthemum coronarium L. is a herbaceous annual weed of winter cereals also grazed by sheep. To evaluate its re-introduction and role, as pasture species, the forage production, nutritive value and self-reseeding capacity of a sowed sward of C. coronarium, a trial was carried out with interdisciplinary approach in Sardinia (Italy) during 1993-95. C. coronarium appears very interesting as forage species and its introduction in forage chains is desirable.
9. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 1997/11/26-29, Badajoz (Spain)